The Influence of Emotional Intelligence, Spiritual Intelligence, and Interpersonal Communication on Teacher Performance - Nabila, Syifa Hasna (Jurnal sosial dan sains, 2025)
This study addresses the issue of inconsistent teacher performance despite increasing professional demands in schools. The objective of this research is to examine the influence of emotional intelligence, spiritual intelligence, and interpersonal communication on the performance of junior high school teachers in Tegowanu District, Grobogan Regency. The study adopts a quantitative approach by distributing questionnaires to 100 teachers from five schools. Data analysis was conducted using validity and reliability tests, multiple linear regression, and t-tests with SPSS version 29. The results indicate that spiritual intelligence and interpersonal communication have a positive and significant impact on teacher performance, while emotional intelligence does not show a significant effect. These findings imply that improving teacher performance requires more than just emotional capacity—it also depends on spiritual values and interpersonal communication skills. Therefore, professional development programs should focus on enhancing teachers’ value-based awareness and communication competencies to foster a more holistic and effective educational environment.